Juridical Analysis of Sustainable Food Agricultural Land Protection Policy in Controlling Land Conversion and Its Impact on the Agribusiness Sector - Enda Maharani; Frans Tory Damara Pradipta; Zitra Akhmad Syahrullah Fadly; Mari Lalang (Punggawa Law Review, 2026)
Agricultural land conversion has become a legal and economic challenge that affects food security and the sustainability of the agribusiness sector. This study aimed to analyze the juridical aspects of Sustainable Food Agricultural Land Protection (LP2B) policy in controlling land conversion and examining its impacts on agribusiness sustainability. This research used a normative juridical method with statutory and conceptual approaches. The study analyzed legal regulations, legal principles, and relevant academic literature related to agricultural land protection. The findings showed that LP2B policy had provided a legal framework through land designation, conversion control mechanisms, incentives, and institutional arrangements. However, the effectiveness of LP2B implementation was still influenced by regulatory synchronization, institutional capacity, and supervision mechanisms. The study also found that agricultural land protection had a significant relationship with agribusiness sustainability because land availability determined production continuity, farmers’ economic stability, and agricultural development. This research emphasized that LP2B should be implemented as an integrated legal instrument connecting agrarian protection, spatial governance, and agricultural economic sustainability.